1995
DOI: 10.1088/0953-8984/7/46/013
|View full text |Cite
|
Sign up to set email alerts
|

A study on fullerene incorporated into a porous silicon matrix (photoluminescence)

Abstract: Samples with low-energy C60 ions implanted into porous silicon were fabricated with the ionized cluster beam deposition approach for improving the light emission of C60. Depth analysis by secondary-ion mass spectroscopy showed that C60 had been incorporated into porous silicon. The photoluminescence spectrum measured under excitation by an Ar+ laser (514.4 nm) at room temperature showed a large number of intense and well resolved fine-structure peaks. These features indicated the strong coupling of vibrational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The existence of a covalent interaction between porous silicon and fullerene molecules can affect the luminescent properties of porous silicon [6,7]. In most investigations, such an effect is manifested only in the passivation action of a fullerene coating which become significant after the annealing of a hybrid layer in the hydrogen atmosphere [5,6].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The existence of a covalent interaction between porous silicon and fullerene molecules can affect the luminescent properties of porous silicon [6,7]. In most investigations, such an effect is manifested only in the passivation action of a fullerene coating which become significant after the annealing of a hybrid layer in the hydrogen atmosphere [5,6].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, it was shown that the deposition of nanostructural carbon layers on the surface of porous silicon substantially (by several orders of magnitude) increases the specific surface area and significantly decreases the surface resistance of a porous material [4]. The subjects of a rising interest are the carbon clusters such as fullerenes, especially C 60 , embedded in a porous silicon matrix [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation